2010
DOI: 10.1024/0301-1526/a000022
|View full text |Cite
|
Sign up to set email alerts
|

Infrapopliteal run-off and the outcome of femoropopliteal percutaneous transluminal angioplasty

Abstract: Compromised postprocedural infrapopliteal run-off predisposes to early restenosis/reocclusion after femoropopliteal PTA. Deterioration of infrapopliteal run-off in the year after femoropopliteal PTA is accompanied by worsening of long-term femoropopliteal patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 15 publications
4
21
2
2
Order By: Relevance
“…Abbreviations as in Figure 1. (13)(14)(15). In this context, results of the present study support findings that the degree of IC is positively affected by successful and long-lasting interventions of IPA lesions (4,5,16).…”
Section: Figure 3 Event-free Survivals In Patients With Critical Limbsupporting
confidence: 92%
“…Abbreviations as in Figure 1. (13)(14)(15). In this context, results of the present study support findings that the degree of IC is positively affected by successful and long-lasting interventions of IPA lesions (4,5,16).…”
Section: Figure 3 Event-free Survivals In Patients With Critical Limbsupporting
confidence: 92%
“…The number of patent tibial vessels at the time of index procedure did not impact limb salvage (p ¼ 0.063). 60 Interestingly, Salapura et al 61 reported early restenosis and reocclusion in patients' limbs with good periprocedural runoff that worsened in the year after PTA. This suggests that loss of tibial runoffs post procedure may have an adverse impact on the long-term outcome of FP treatment.…”
Section: Procedural Factorsmentioning
confidence: 99%
“…In our study on the effect of tibial runoff on femoropopliteal patency after PTA [22], consecutive consenting patients with claudication or critical limb ischemia admitted for femoropopliteal PTA to the Department of Vascular Diseases of the University Medical Centre Ljubljana have been enrolled and prospectively followed up. In addition to femoropopliteal PTA, infrapopliteal PTA has been performed in all cases when lesions of the calf arteries have been judged suitable for intervention.…”
Section: Methodsmentioning
confidence: 99%